Social Intelligence and Media Literacy of Senior High School Students - Telen, Jeric L.; Maitem, John Michael Z.; Bete, Jed I. (International Journal Corner of Educational Research, 2024)
This study aimed to determine the relationship between social intelligence and media literacy of senior high school students. A correlational design was used in this study. It was participated by 300 senior high school students. A survey questionnaire on social intelligence and media literacy were used as instruments. Mean and Pearson correlation coefficient were used to analyze the data. This study revealed that social intelligence of students is high which means that students can read other people and understand their intentions and motivations. Likewise, media literacy of senior high school students is high which implies students are good in perceiving the use of media and are aware of its negative and positive use. Furthermore, there is a moderate positive correlation between social intelligence and media literacy. This may further imply that a higher social intelligence can improve media literacy. Thus, the conduct of social intelligence enhancement program is recommended to improve the media literacy of the students.